Screening and Functional Verification of Selectable Marker Genes for Cordyceps militaris - Haiwei Lou; Yu Zhao; Renyong Zhao; Zhiwei Ye; Junfang Lin; Liqiong Guo (Journal of Food Quality)
The selectable marker genes are necessary resistance genes for gene knockout, gene complementation, and gene overexpression in filamentous fungi. Moreover, the more sensitive the filamentous fungi are to antibiotics, the more helpful it is to screen the target transformants. In order to obtain the antibiotic (or herbicide) which can effectively inhibit the growth of Cordyceps militaris and verify the function of the corresponding resistance gene in C. militaris, the sensitivity of C. militaris to hygromycin and glufosinate ammonium was compared to determine the resistance gene that was more suitable for the screening of C. militaris transformants. The binary vector of the selectable marker gene was constructed by combining the double-joint PCR (DJ-PCR) method and the homologous recombination method, and the function of the selectable marker gene in C. militaris was verified by the Agrobacterium tumefaciens-mediated transformation method. The results showed that C. militaris was more sensitive to glufosinate ammonium than hygromycin. The growth of C. militaris could be completely inhibited by 250 μg/mL glufosinate ammonium. The expression cassette of the glufosinate ammonium resistance gene (bar gene) was successfully constructed by DJ-PCR. The binary vector pCAMBIA0390-Bar was successfully constructed by homologous recombination. The bar gene of the vector pCAMBIA0390-Bar was successfully integrated into the C. militaris genome and could be highly expressed in the transformants of C. militaris. This study will promote the identification of C. militaris gene function and reveal the biosynthetic pathways of bioactive components in C. militaris.